(untitled) (Journal of Advances and Scholarly Researches in Allied Education, 2012)
Monetarypolicyis the process by which the monetary authority of a country controls the supplyof money, often targeting a rate of interest for the purpose of promotingeconomic growth and stability. The official goals usually include relativelystable prices and low unemployment. Monetary theory provides insight into howto craft optimal monetary policy.